PENGARUH PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT (PNPM) MANDIRI PEDESAAN DALAM PENINGKATAN PENDAPATAN PADA USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI UPK KECAMATAN TELUK BAYUR KABUPATEN BERAU: PENGARUH PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT (PNPM) MANDIRI PEDESAAN DALAM PENINGKATAN PENDAPATAN PADA USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI UPK KECAMATAN TELUK BAYUR KABUPATEN BERAU - ira indriani (ECO-BUILD, 2022)
The purpose of this study was to determine whether there was an effect of the Rural Mandiri National Community Empowerment Program (PNPM) on increasing incomes for Micro, Small and Medium Enterprises in UPK Teluk Bayur District, Berau Regency. The type of research used is field research with the method used in the form of interviews, questionnaires and documentation to the PNPM Mandiri Rural Activity Management Unit (UPK) Teluk Bayur District which consists of the chairman, secretary and treasurer, as well as people who are directly involved in the resources. primary data. The data analysis technique used is simple linear regression using the SPSS 21.0 application, with the independent variable being the National Community Empowerment Program (PNPM) and the dependent variable is Income Increase in Micro, Small and Medium Enterprises, and the regression results are Y = 4.806 + 0.877 X. The results showed that the Mandiri Rural Community Empowerment National Program (PNPM) had a significant and positive influence on the Income of Micro, Small, and Medium Enterprises under the management of the UPK. The Mandiri Rural National Program for Community Empowerment (PNPM) had a 94% relationship with Business Income. Micro, Small and Medium Enterprises (MSMEs) in the UPK Teluk Bayur District.